RELASI SOSIAL DALAM AL-QUR’AN - M. Agus Yusron (TAFAKKUR : Jurnal Ilmu Al-Qur'an dan Tafsir, 2023)
Restrictions on social relations are still widely found in the midst of a multicultural world society. Nation, religion, race, ethnicity, language, and skin color often become barriers between individuals or communities interacting with each other, even discrimination to intimidation becomes the end of the bad relations that occur. The Qur'an, which is hudan linnâs, certainly does not allow disharmonious relations between humans to occur, because it contradicts the purpose of sending humans as executors of life, caretakers of the earth, and preservers of the universe. So it is necessary to trace the verses that discuss social relations; either implicitly or explicitly. The method used in this research is a qualitative method, using a library approach (library reseacrh). Researchers try to trace the verses related to social relations, then analyze and display the interpretations or arguments of experts. In general, this study found that social relations in the Qur'an cover all aspects of life, not limited to space and time, religion, ethnicity, race, language, nation, or skin color. There is an obligation to build good social relations for each individual towards their parents, children, neighbors, the wider community, fellow religions, or even between religions. The Qur'an fully emphasizes social relations among Muslims, then relaxes social relations between religions on the condition that they do not fight or bring no harm to them.